Decolonizing theology - Ward, G (Pieter de Waal Neethling Trust, 2017)
In this essay, the author aims to deal with two questions, namely (1) how decolonized is South African theology? And if there is a sense that South African theology needs to decolonized, then the second question is (2) how should this be done? Te frst is raised as an interrogative starting-point, and is therefore not conclusive, since the author is admittedly, not fully versed in South African theology. Tus, the main body of the work is concerned with the second question, and thus proposes a three-stage method for decolonizing theology in South Africa. Te frst involves ‘provincializing’ the Western context as a background for doing theology in the Global South. Te second concerns the ‘translation’ of concepts into the difering contexts where theology is produced, and the third is related to the question of ‘afrmation’, in the sense of positively acknowledging culture as being refective of the diversity of people groups. Te author closes with some refections on theological task today, specifcally as this relates to mission, the defnition of tradition, and its connection to the academy.